2022
DOI: 10.3390/ijms232012186
|View full text |Cite
|
Sign up to set email alerts
|

TcMYB8, a R3-MYB Transcription Factor, Positively Regulates Pyrethrin Biosynthesis in Tanacetum cinerariifolium

Abstract: Pyrethrins are a mixture of terpenes, with insecticidal properties, that accumulate in the aboveground parts of the pyrethrum (Tanacetum cinerariifolium). Numerous studies have been published on the positive role of MYB transcription factors (TFs) in terpenoid biosynthesis; however, the role of MYB TFs in pyrethrin biosynthesis remains unknown. Here, we report the isolation and characterization of a T. cinerariifolium MYB gene encoding a R3-MYB protein, TcMYB8, containing a large number of hormone-responsive e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…Accordingly, EPS not only stimulates the expression of ABA and GA key enzyme genes ( GA2ox and CYP707A ) in S. baicalensis calli but also promotes the expression of MYB3 , MYB8 , and MYB13 . Based on our experimental results and relevant literature ( Bang et al., 2008 ; Yuan et al., 2013 , 2015 ; Qian et al., 2020 ; Zhou et al., 2022 ; Fang et al., 2023 ; He et al., 2023 ), EPS treatment induces flavonoid synthesis in S. baicalensis calli by regulating the expression of phytohormones, TFs, and enzymes. That is, EPS might stimulate the expression of genes encoding MYB3, MYB8, MYB13, GA2ox, and CYP707A, leading to significantly higher expression of CHS , CHI , FNS , and F6H and ultimately promoting the synthesis of flavonoids.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…Accordingly, EPS not only stimulates the expression of ABA and GA key enzyme genes ( GA2ox and CYP707A ) in S. baicalensis calli but also promotes the expression of MYB3 , MYB8 , and MYB13 . Based on our experimental results and relevant literature ( Bang et al., 2008 ; Yuan et al., 2013 , 2015 ; Qian et al., 2020 ; Zhou et al., 2022 ; Fang et al., 2023 ; He et al., 2023 ), EPS treatment induces flavonoid synthesis in S. baicalensis calli by regulating the expression of phytohormones, TFs, and enzymes. That is, EPS might stimulate the expression of genes encoding MYB3, MYB8, MYB13, GA2ox, and CYP707A, leading to significantly higher expression of CHS , CHI , FNS , and F6H and ultimately promoting the synthesis of flavonoids.…”
Section: Discussionmentioning
confidence: 72%
“…For example, Yuan et al (2013) showed that GA metabolism contributes to flavonoid biosynthesis, with the expression of MYB8 significantly improving in S. baicalensis within 3 h of GA treatment. Furthermore, ABA can improve the expression of MYB3 and MYB8 in a relatively short period of time (Bang et al, 2008;Zhou et al, 2022). Accordingly, EPS not only stimulates the expression of ABA and GA key enzyme genes (GA2ox and CYP707A) in S. baicalensis calli but also promotes the expression of MYB3, MYB8, and MYB13.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SiMYB75 positively regulates the responses to drought, salt, and osmotic stress through an ABA-mediated pathway [83]. TcMYB8 and SbMYB12 can respond to MeJA treatment [84,85], and GlMYB4 and GlMYB88 play important roles in the synthesis of flavonoids mediated using MeJA signaling [86]. In this study, we found that regulatory elements associated with MeJA and ABA were most common in EfMYB; thus, we also analyzed the expression characteristics of the nine EfMYB genes after ABA and MeJA treatments.…”
Section: Discussionmentioning
confidence: 88%
“…The expression vector pGreenII62-SK was driven by the CaMV35S promoter and the constructed pGreenII62-SK: TcbHLH14 vector was transformed into A. tumefaciens GV3101 (containing the pSoup19 vector). Transient transformation of T. cinerariifolium leaves was performed as described previously [ 46 ]. After the RT-qPCR assay, 4-day-old leaves were taken for HPLC analysis.…”
Section: Methodsmentioning
confidence: 99%